EFEKTIFITAS MASSAGE ENDORPHIN UNTUK MENGURANGI NYERI PUNGGUNG IBU HAMIL TRIMESTER III - Meilany Laisouw; Ratna Malawat (Poltekkes Kemenkes Maluku, 2026)
During pregnancy, physiological and psychological changes occur, these changes occur as a form of body adaptation to the growth and development of the fetus during pregnancy3. The result of physiological and psychological changes causes pregnant women to experience discomfort that is felt from the first to third trimester. One of the discomforts felt in the third trimester is back pain. Globally, back pain in pregnant women is a significant health problem. WHO noted that around 24%-90% of pregnant women experience back pain during pregnancy, with around 25% of complaints continuing into the postpartum period. The research design used in this study was a quasi-experiment with a pretest-posttest approach with a control group. The instrument used to measure pain intensity was the NRS (Numeric Rating Scale) scale sheet. The data were collected and then analyzed to obtain the results of an independent sample t-test regarding the difference in back pain in pregnant women in the third trimester before and after the intervention between the treatment group given Endorphin Massage and the control group given standard services to pregnant women showed a p value = 0.000, so it was interpreted that there was a significant difference in reducing back pain between the two groups. It appears that there was a significant decrease in the group given Endorphin Massage, so it is recommended that health workers promote and teach non-pharmacological methods such as endorphin massage which can reduce discomfort during pregnancy so that pregnant women can take initial action when they feel discomfort.